Mining and Visualization of Tourism Cultural Image Based on the Information Transmission Model of Tourism Cultural Map—Taking Nanjing Xuanwu Lake Tourist Attraction as an Example - Haoyu Yang; Jie Shen; Shuai Hong; Fengzhen Zhu (ISPRS International Journal of Geo-Information)
Tourism cultural image is vital for conveying the cultural essence of a destination, enhancing tourists’ cultural understanding and engagement. However, traditional tourism cultural maps often face challenges in clearly defining cultural themes and effectively communicating cultural and emotional information to users. To address these issues, we propose an improved information transmission model for a tourism cultural map to optimize the communication pathway between cartographers and map users. Based on this model, we introduce a method for mining and visualizing tourism cultural image using tourist attractions as the focal points. Then, based on the visualization results, we discuss the selection of map expression objects and the framework of map visualization design. Finally, we give an implementation process of a tourism cultural map of tourist attractions based on mining and visualization of tourism cultural image. To verify the method’s feasibility, we developed a mobile interactive tourism cultural map application using Xuanwu Lake in Nanjing, China, as an example. The results demonstrate the method’s effectiveness in tourism cultural image mining and visualization, provide solutions to the problems of traditional tourism cultural maps, and help tourists’ understanding of the culture of tourist attractions.